Ptosis Spectacle - Kumar, Narendra (Canadian Journal of Optometry, 2008)
The condition of Ptosis is discussed with its classifi cation and management by surgery, scleral contact lenses and ptosis crutch. The method of the making of the ptosis spectacle - using a nylon thread support that is effective, comfortable, and reasonably inconspicuous – is explained.